The Standby Book. Activities For the Language Classroom - Lindstromberg, Seth. (Cambridge Cambridge University Press, 1997)
The Standy Book is an anthology of more than 100 language learning activities contributed by 33 teachers. It includes complete lesson suggestions, activities which can be used to build complete lessons, suggestions for variations and extensions of the activities, as well as sample material.
Keywords: Teaching English